การศึกษาเปรียบเทียบการตัดสินใจลงทุนระหว่างโครงการผลิตเหล็กเส้นกลม และเหล็กรีดซ้ำ - ประวิทย์ รัตนพิเชฐกุล (จุฬาลงกรณ์มหาวิทยาลัย, 1980)
Planning is essentially a form of design and may be defined as exploration projection and evaluation of ideas. There are plenty of ways for accomplishing a contemplated end, literally invented and evaluated on various bases. The conception of trying different ways to achieve a desired end does not at first appear to be a logical process as it is time-consuming but it is generally agreed that the evaluation is largely a matter of reasoning. One important aspect of planning is that it encourages trial of great many ideas on paper more or less conclusively before putting them in practice. Planning analysis is usually concerned with alternatives involving prospective outputs and inputs at specific points in a definite period of time. These outputs and inputs are then converted into monetary receipts and disbursements, insofar as this conversion is possible. The resulting information is quantitative in nature and therefore, may be manipulated mathematically for concrete comparison. This thesis involves the factors to be taken into account in determining the choice between producing round bars or re-rolled bars. It must be noted that the thesis will concentrate only on the steel plants with maximum capacity of 30,000 metric tons per annum. Under macro study, investment in steel bar industry is not encouraged at the moment due to surplus capacity of existing steel plants. However, from the case study of 2 investment projects on round bars and re-rolled bars, it is found that the net present values of the round bars manufacturer and re-roled bars manufacturer are approximately 30,672,000 baht and 25,060,000 baht respectively. Measurements indicating comparative profitability prospects on both products are as follows:- Gross Profit Margin (average) Round Bars Manufacturer 28.47% Re-Rolled Bars Manufacturer 20.73% Net Profit Margin (average) Round Bars Manufacturer 6.51% Re-Rolled Bars Manufacturer 4.50% Return on Assets (average) Round Bars Manufacturer 14.61% Re-Rolled Bars Manufacturer 11.80% Return on Net Worth (average) Round Bars Manufacturer 21.00% Re-Rolled Bars Manufacturer 19.66% Net Present Value (Baht) Round Bars Manufacturer 30,672,000 Re-Rolled Bars Manufacturer 25,060,000% Break-even Point as % of Sales Round Bars Manufacturer 94-27% Re-Rolled Bars Manufacturer 81-21% Rate of return method is probably the most common practice for comparing a concerte proposal with other opportunities believed to exist. The net present value method is one universal measurement of financial success used in deciding whether or not to accept the proposals. Financial analysis is not only indicator for viability of projects unless comprehensive study on both technical and marketing aspects have been conduted. In other words, investment strategy in any project needs the studies of both internal and external factors.